ANTIPLASMODIAL ACTIVITIES OF THE STEM BARK EXTRACT OF ARTOCARPUS ALTILIS FORSBERG - ALADESANMI, Adetunji Joseph; Odiba, Ogu Emmanuel; ODEDIRAN, Samuel Akintunde; Oriola, Ayodeji Oluwabunmi (African Journal of Infectious Diseases (AJID), 2022)
Background: The potential of Artocarpus altilis stem bark as a safe antimalarial agent, and the identification of its antimalarial constituents was explored. Materials and Methods:The air-dried stem bark was extracted with 70% ethanol, filtered and concentrated in vacuo to obtain the extract (EE). The extract was successively partitioned to give n-hexane (AAH),dichloromethane (AAD), ethyl acetate (AAE)n-butanol (AAB)and aqueous (AAQ)fractions respectively after determining the acute toxicity using Lorke’s method. These were each evaluated for chemosuppressive antimalarial activities (0-200mg/kg) against chloroquine-sensitive Plasmodium berghei-berghei-infected albino mice. Normal saline and chloroquine, 10 mg/kg were negative and positive control respectively.The survival times and percentage survivors of the mice in both experiments were determined after observation for twenty-eight days post-drug administration. The five (5) column chromatographic (CC) fractions, AAH1, AAH2, AAH3, AAH4andAAH5 obtained from the most active AAH, were also evaluated for antimalarial activities (0-50mg/kg). Further column purification and repeated PTLC of AAH5 yielded three bands, which were finally subjected to GC-MS analysis. Results:EE gave ED50 and LD50 values of 227.17and >5000 mg/kg while its partitioned fractions gave ED50 values as follows: AAH, 79.14; AAD, 215.59;AAE, 160.46,AAB,81.42; and AAQ, 90.85 mg/kg respectively. The primary CC fractions also gave ED50 values as follows:AAH1 21.95;AAH2, 26.96;AAH3,21.30; AAH4, 20.92 andAAH5, 20.75 mg/kg respectively to identify AAH5 as the putative fraction. GC-MS analysis revealed eleven major compounds (1–11) in the three PTLC bands as the antiplasmodial constituents of the plant. Conclusion:The stem bark of A. altilis is a potential agent in malaria control which is safe for oral use.